2019
DOI: 10.1111/nup.12262
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and caring: Towards a Marxist understanding of nursing work

Abstract: The aim of this paper is to re‐examine nursing work from a Marxist perspective by means of a critique of two key concepts within nursing: autonomy and caring. Although Marx wrote over 150 years ago, many see continuing relevance to his theories. His concepts of capital, ideology and class antagonism are employed in this paper. Nursing's historical insertion into the developing hospital system is seen in terms of a loss of autonomy covered over by the development of cults of loyalty toward those institutions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
10
0
6
Order By: Relevance
“…Around the same time, nursing theorists such as Jean Watson ( 1979 ) and Madeleine Leininger ( 1978 ) developed theories of caring that concentrated on caring as the defining attribute of the nursing profession. By the 1980s, caring was positioned as intrinsic to the nursing profession by many theorists (Meleis, 2012 ; Paley, 2002 ; Traynor, 2019 ). In fact, Dunlop ( 1986 ) noted that the emergent caring theories of the 1980s could be linked back to the concept of love in the private domain of the Victorian Era.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around the same time, nursing theorists such as Jean Watson ( 1979 ) and Madeleine Leininger ( 1978 ) developed theories of caring that concentrated on caring as the defining attribute of the nursing profession. By the 1980s, caring was positioned as intrinsic to the nursing profession by many theorists (Meleis, 2012 ; Paley, 2002 ; Traynor, 2019 ). In fact, Dunlop ( 1986 ) noted that the emergent caring theories of the 1980s could be linked back to the concept of love in the private domain of the Victorian Era.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of caring theory and the discourse of caring remains linked to the profession of nursing in subtle but important ways. For example, the expectation that nurses sacrifice themselves for their patients and the healthcare system remains an oft‐unspoken but recognizable element of the nursing profession (see Beard, 1999; Ciezar‐Andersen & King‐Shier, 2021; Emerson, 2017; Goodolf, 2018; Langtree et al, 2020; Mohammed et al, 2021; Moradi et al, 2020; Pask, 2005; Rickett, 2010; Traynor, 2019; Valiani, 2013). Caring theorists in the nursing field point to sacrifice as a meaningful and important component of the nursing process (Helin & Lindström, 2003; Watson, n.d.; Watson et al, 2019).…”
Section: History Of the Presentmentioning
confidence: 99%
“…In the present study, the mean scores of the nurses with master's degree obtained from the Individualized Care Scale‐Nurse version and its three sub‐dimensions were statistically more significant than were those of the other nurses ( p < 0.01), which suggests that the nurses' autonomy reflecting their independence in the provision of care increased as their level of education increased. In some studies conducted with nurse participants, it was emphasized that as the persons' education level increased so did their autonomy levels (Avci & Yilmaz, 2021; Traynor, 2019). This result of the study revealed that nurses using their autonomy while caring for patients, apply more individualized care.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing care focuses on the humanistic and holistic care philosophy that evaluates a sick or healthy individual together with his/her family and environment (Lamb & Pesut, 2021). In the process of individualized care, it is possible to implement the belief and respect that a human being has individuality, integrity, and the right to receive a high level of health service within the frame of nurses' professional values and patients' personal values (Aydin & Büyükbayram, 2020; Peacock‐Johnson, 2018; Traynor, 2019). In the literature, it is stated that individualized care not only contributes to patient satisfaction, quality of life, and improvement of patient autonomy (Avci & Yilmaz, 2021; Aydin & Büyükbayram, 2020), but also increase the quality of nursing care and motivation and job satisfaction in nurses, and supports ethical behaviors (Peacock‐Johnson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cada idoso precisa ser percebido em suas necessidades individuais e o cuidado se apresenta com o sentido de complementar as fragilidades, vulnerabilidades e limitações individuais, ao mesmo tempo em que preserva e amplia funcionalidades e capacidades. Nessa relação, a centralidade no sujeito garante a autonomia de quem oferece o cuidado, mas também de quem o recebe, e estabelece um espaço de interdependência entre os envolvidos(OSHODI et al, 2019;PARANHOS;ALBUQUERQUE;GARRAFA, 2017;TRAYNOR, 2019).O cuidado centrado no idoso utiliza a seu favor a tomada de decisão do paciente na elaboração do cuidado, diminui a resistência e favorece a adesão. Além disso, o idoso percebe o cuidado como uma busca pelo seu bem, com preservação de sua intimidade e interioridade.…”
unclassified